AN OFFENSIVE SET PLAY: OPTIONS AND ADJUSTMENTS - Vitucci, Francesco (Sport- és Egészségtudományi füzetek, 2026)
Every coach has their plays and own system, but we must consider that several systems work. There are always standards in basketball, which are fashionable offensive systems in a given period. Even if these standards are not part of our philosophy, we will still face these standards in defence. Therefore, we have to think about incorporating them into our practice methodology. For example, the ghost screen is prevalent in today’s basketball. Hence, even if it is not part of our offensive strategy, we still need to work on it because we must create defensive rules against it. Zipper-middle pick and roll action is another significant standard. When working on it, we split the system into three parts.